14 Peak troponin T in STEMI: a predictor of all-cause mortality and left ventricular function. (16th October 2019) - Khullar, N; Buckley, A; O'Connor, C; Ibrahim, A; Ibrahim, AIA; Cahill, C; Ahern, C; Arnous, S; Kiernan, T
Abstract : Background: Atherosclerotic cardiovascular disease contributes substantially to morbidity and mortality worldwide. High-sensitivity cardiac troponin T (hs-cTnT) has become an essential tool in the initial management of acute myocardial infarction. Several, but not all studies, have demonstrated worse clinical outcomes with higher troponin levels in non-ST-elevation myocardial infarction (NSTEMI). However, outcomes associated with peak troponin levels following ST-elevation myocardial infarction (STEMI) have not been well established. Purpose: To determine the prognostic value of elevated hs-cTnT in the prediction of all-cause mortality and left ventricular ejection fraction (LVEF) in STEMI. Methods: Single-centre retrospective observational study was conducted of all patients with STEMI between January 2015 and December 2017. False activations of the catheterisation laboratory were excluded. Demographics and clinical data were obtained through electronic patient records. Relationship between peak hs-cTnT and all-cause mortality at 30 days and 1 year, and LVEF was examined. Standard Bayesian statistics were employed for analysis. Results: 568 patients presented with STEMI during this period (186 in 2015, 194 in 2016 and 188 in 2017). Baseline characteristics are shown in table 1 . Mean age was 63.6 years (SD 12.0) and 76.4% were male. Culprit vessels included: 220 (38.7%) Left anterior descending (LAD), 227 (40.0%) Right coronary artery, 95 (16.7%) Circumflex, 7 (1.2%) Left main stem, 1 (0.2%) Ramus and 18 (3.2%) multi-vessel or undetermined culprit. 535 (94.2%) underwent primary percutaneous coronary intervention, 12 (2.1%) urgent coronary artery bypass and 21 (3.7%) were treated medically. Mean peak hs-cTnT was 5124 ng/L for the cohort (range 20 – 57875 ng/L) (reference range <14 ng/L). Peak hs-cTnT measured at a median of 1 day from admission. Mean creatinine was 95.6 μmol/L. All-cause 30-day mortality rate was 6.2% and all-cause 1-year mortality rate was 8.8%. Mean peak hs-cTnT levels were significantly higher in those who died within 30 days compared with those who survived (12238 ng/L vs. 4657 ng/L respectively, p<0.001). Peak hs-cTnT levels were also significantly higher in those who died within 1 year compared with those who survived (10319 ng/L vs. 4622 ng/L respectively, p<0.001). One-way ANOVA exhibited significant differences in peak troponin between culprit vessels. LAD was associated with the highest hs-cTnT and was the most common culprit in those who died at 1 year. An inverse relationship was demonstrated between peak hs-cTnT and LVEF (Pearson's R=0.379, p<0.00001; figure 1 ). Conclusion: In STEMI, those who died at 30 days and 1 year had significantly higher peak troponin levels than those who survived. Peak troponin is also inversely proportional to LVEF with higher troponins associated with lower LVEF. While the cost-effectiveness of performing routine troponins in STEMI is arguable, there may be a rationale for performing a single troponin sample at 24 hours post admission as a predictor of mortality and LVEF. Data represent the number (percentage) of [patients or median [interquartile range]. Mann-Whitney U test was used for comparisons of continuous variables; Fishers's exact test was used for categorical variables.